Impacts of Lower Thermospheric Atomic Oxygen and Dynamics on the Thermospheric Semiannual Oscillation Using GITM and WACCM‐X. Issue 2 (8th February 2022) - Malhotra, Garima; Ridley, Aaron J.; Jones, McArthur
Abstract: The latitudinal and temporal variation of atomic oxygen (O) is opposite between the empirical model, NRLMSISE‐00 (MSIS) and the whole atmosphere model, whole atmosphere community climate model with thermosphere and ionosphere extension (WACCM‐X) at 97–100 km. Atomic Oxygen from WACCM‐X has maxima at solstices and summer mid‐high latitudes, similar to [O] from Sounding of the Atmosphere using Broadband Emission Radiometry (SABER). We use the densities and dynamics from WACCM‐X to drive the Global Ionosphere Thermosphere Model (GITM) at its lower boundary and compare it with the MSIS driven GITM. We focus on the differences in the modeling of the thermospheric and ionospheric semiannual oscillation (T‐I SAO). Our results reveal that driving GITM with WACCM‐X causes the T‐I SAO to maximize around solstices, opposite to when MSIS is used. This is because the global mixing in GITM during solstices is not strong enough to decrease the solstitial [O] densities below the equinoctial values between mesosphere and lower thermosphere (MLT) and upper thermosphere. Larger summer [O] in the MLT leads to the accumulation of [O] at lower latitudes in the thermosphere due to weaker meridional transport, which further increases the amplitude of the oppositely phased SAO. WACCM‐X itself has the right phase of SAO in the upper thermosphere but wrong at lower altitudes. The exact mechanisms that can correct the phase of T‐I SAO in GITM while using SABER‐like [O] in the MLT are currently unknown and warrant further investigation. We suggest mechanisms that can reduce the solstitial maxima in the lower thermosphere, for example, stronger interhemispheric meridional winds, stronger residual circulation, seasonal variations in eddy diffusion, and momentum from breaking gravity waves. Plain Language Summary: We study the characteristics and drivers of the Thermospheric and Ionospheric Semiannual Oscillation (T‐I SAO) using a numerical model of the Earth's upper atmosphere. It is an oscillation in T‐I densities, temperature, and composition with maxima at equinoxes. We investigate the contribution of lower atmosphere to the T‐I SAO using different assumptions at the lower boundary of the model. We find that using the correct lower boundary conditions changes the phase of T‐I SAO such that it does not match with the satellite observations at higher altitudes. This implies that there are mechanisms missing in the numerical model that can reproduce the correct SAO phase while using the updated boundary conditions. Key Points: Atomic oxygen in mesosphere and lower thermosphere (MLT) from Sounding of the Atmosphere using Broadband Emission Radiometry and whole atmosphere community climate model with thermosphere and ionosphere extension (WACCM‐X) has a semiannual oscillation (SAO) with maxima at solstices and at summer mid‐high latitudes, opposite to that of MSIS Global Ionosphere Thermosphere Model (GITM) reproduces the T‐I SAO with equinoctial maxima using MSIS [O] at lower boundary and with solstitial maxima using WACCM‐X [O] GITM does not change the SAO phase between MLT and upper thermosphere on a seasonal scale